2014
DOI: 10.1007/s11356-014-3285-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of essential oils mixture on performance, eggshell quality, hatchability, and mineral excretion in quail breeders

Abstract: The main aim of this study was to investigate the effect of six different levels (0, 50, 100, 200, 400, and 600 mg/kg) of phytogenic feed additive containing a mixture essential oils from thyme, black cumin, fennel, anise and rosemary on performance, eggshell quality, reproductive traits, and mineral excretion in quail breeders. In this trial, a total of 60 male and 120 female quails, 91 days old, were randomly distributed in six experimental groups. During the 60-day experiment period, birds were fed with six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Body weight, egg production, and egg weight were not affected by dietary treatments. This result is similar to several studies on layer hens (Kaya et al, 2013) and quail breeders (Olgun and Yıldız, 2014). The study of Çabuk et al (2014) also revealed similar findings on egg weight by using dietary fennel essential oil including mixture for laying hens at the summer season.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Body weight, egg production, and egg weight were not affected by dietary treatments. This result is similar to several studies on layer hens (Kaya et al, 2013) and quail breeders (Olgun and Yıldız, 2014). The study of Çabuk et al (2014) also revealed similar findings on egg weight by using dietary fennel essential oil including mixture for laying hens at the summer season.…”
Section: Discussionsupporting
confidence: 90%
“…The numerical differences in egg production in the groups were not significant when compared with the control group. The result of egg production is similar to results of Nasiroleslami and Torki (2010) and Olgun and Yıldız (2014). However, dietary 50 mg/kg fennel extract increased the egg production of broiler breeders (Kazemi-Fard et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result agrees with that of Olgun (2016) who confirmed that eggshell thickness was increased quadratically by EO supplementation. On the contrary, some studies reported that supplementation of EOs in laying hen diet had no effect on the egg quality parameters ( Luna et al., 2012 ; Olgun and Yıldız, 2014 ). However, the improvements in HU in our study are important for the egg-food industry because the HU score is known as an indicator of egg freshness and is related to shelf life.…”
Section: Discussionmentioning
confidence: 94%
“…And, Olgun (2016) also reported that egg weight, egg mass and eggshell thickness were positively affected by EOM supplementation. On the contrary, research also showed that the different dietary levels of EOM had no significant effect on performance parameters, damaged eggs, eggshell weight ( Olgun and Yildiz, 2014 ). However, these previous studies on the EOs in the layers were mainly focused on the production performance, egg quality and nutrient digestibility, and the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%